Overview of Chagas disease surveillance in an endemic region in Southeastern Brazil - Rafael , Aline Ferreira; Ferreira, Raquel Aparecida; Mota, Ariela Ferreira; Damasceno, Renata Fiúza; Menezes, Agna Soares da Silva; Lopes, Bartolomeu Teixeira; Paulo, Gustavo Libério de; Sabino, Ester Cerdeira; Ribeiro, Antônio Luiz Pinho; Quintino, Nayara Dornela; Vieira, Thallyta Maria (Revista do Instituto de Medicina Tropical de São Paulo, 2023)
Chagas disease (CD) is a neglected disease caused by the protozoan Trypanosoma cruzi. It has high morbidity and mortality rates and mainly affects socially vulnerable populations. This is a cross-sectional study, with retrospective and prospective data collection. Using questionnaires applied to environmental surveillance coordinators, we characterized the status of CD surveillance activities in municipalities endemic for the disease in Northern Minas Gerais State (MG) and Jequitinhonha Valley (Vale do Jequitinhonha). Moreover, we spatialized the vulnerability index for chronic CD in the study area. The population consisted of 22 environmental surveillance coordinators, active in 2020, from Northern MG and Jequitinhonha Valley, 21 municipalities included in the SaMi-Trop research project, and Montes Claros municipality. After applying the questionnaires to the coordinators, a descriptive analysis of the variables was performed. To characterize the active municipalities, the explanatory variables collected in the questionnaire were compared with the dichotomous variable. Bivariate descriptive analysis was performed. Finally, geoprocessing techniques were used to spatialize the data and prepare maps. Regarding the team of endemic combat agents (ECA), 90.9% reported the lack of a specific team for CD vector control actions. Of the 22 municipalities participating in this study, nine were active (41.1%). Only 25% (n=2) of active municipalities (9% of the municipalities studied) met the target of visiting 50% of households per year. Finally, 81.1% of the coordinators stated that in their municipality, they developed actions linked to primary health care (PHC). The implementation of CD surveillance activities weakened in the endemic region. Few municipalities have a surveillance team, with low regularity of active surveillance and noncompliance with the program’s goal. The results suggest insufficient recording of activities in the information system, considering that there are municipalities that report performing the activities, but no production record was observed in the system.